Evaluation of contrast Sonazoid-enhanced ultrasonography for the detection of hepatic metastases in breast cancer - Mishima, Mai (Breast Cancer, 2014)
BACKGROUND: The present study was aimed to evaluate the usefulness of contrast Sonazoid-enhanced ultrasonography (US) for the detection of hepatic metastases in breast cancer patients and compare the clinical efficacy and sensitivity of this technique with conventional contrast unenhanced B-mode US in follow-up examinations of breast cancer patients with liver metastasis. METHODS: We assessed a total of 84 hepatic tumors from 24 patients diagnosed with or suspected of having metastatic cancer. These hepatic nodules were diagnosed through imaging, including dynamic magnetic resonance imaging (MRI), contrast-enhanced computed tomography (CECT) scan, B-mode US or contrast Sonazoid-enhanced US (SEUS). Differences in the sensitivity between US and SEUS were compared using MR imaging, CECT, and follow-up imaging. RESULTS: A total of 79 nodules were diagnosed as metastatic tumors. The remaining nodules were diagnosed as benign tumors (hepatic hemangioma: n = 3; local fatty change: n = 2). SEUS precisely detected the presence or absence of hepatic tumors in the 24 patients examined, showing a sensitivity of 98.8 % (83 of 84 lesions) for total imaged solid liver lesions, with an accuracy of 98.7 % (78 of 79 lesions) for total metastatic breast cancer lesions. In contrast, conventional B-mode US imaging revealed hepatic tumor lesions at a sensitivity of 66.7 % (56 of 84 lesions) and an accuracy of 64.6 % (51 of 79 lesions), respectively. Furthermore, the false positive and false negative rates were, respectively, 6.33 and 29.1 % for B-mode US and 0 and 1.3 % for SEUS. Moreover, twenty-seven metastatic tumors and five benign lesions (3 hemangiomas and 2 focal fatty changes/sparings) were imaged using SEUS but not conventional B-mode US. Significant differences in diagnostic accuracy rates between contrast Sonazoid-enhanced US and conventional B-mode US were observed (Wilcoxon signed rank test: p = 0.0009). No severe adverse events occurred during SEUS after the administration of Sonazoid, except for a grade 1 skin reaction and nausea in one patient. CONCLUSION: These results suggested that Sonazoid could be safely administrated to breast cancer patients with liver metastatic disease. Thus, contrast Sonazoid-enhanced US is a feasible and more effective method than B-mode US for the detection of hepatic metastasis, particularly for small metastatic breast cancer lesions less than 14 mm in diameter, showing significant high sensitivity and accuracy.